Rational design of an ITO/CuS nanosheet network composite film as a counter electrode for flexible dye sensitized solar cells. Issue 34 (15th August 2016) - Zhang, Xiaojia; Liu, Xingqiang; Zhang, Yupeng; Bao, Rongrong; Peng, Dengfeng; Li, Tianfeng; Gao, Guoyun; Guo, Wenxi; Pan, Caofeng
Abstract : The brittleness of traditional indium-doped tin oxide (ITO) is an obstacle to its commercialization in flexible opto-electronics. Abstract : The brittleness of traditional indium-doped tin oxide (ITO) is an obstacle to its commercialization in flexible opto-electronics. Here, we report a flexible ITO/CuS nanosheet network (NN) composite conductive film, with appreciable transparency, by employing a combined electrospinning and sputtering method. 6% power conversion efficiency (PCE) was achieved from the fabricated high-performance flexible dye-sensitized solar cell, in which the ITO/CuS NN composite film serves as the counter electrode and titanium dioxide nanotube arrays (TNARs) as the photoanode. After 200 bending cycles, the PCE presents negligible changes in PCE. The composite films exhibit robust flexibility and electrochemical catalytic properties by taking advantage of CuS NN. We believed that the rationally designed ITO/CuS NN composite transparent conductive electrode can be a promising candidate in portable and wearable electronics.